Patients suffering due to complicated Peritonitis may not benefit from Splenectomy: clinical data from a retrospective study - Lichtenstern, Christoph; Zimmermann, Johannes B.; Rahbari, Nuh Nabi; Uhle, Florian; Kerber, Stefanie; Weismüller, Katja; Hofer, Stefan; Walter, Valentin; Bruckner, Thomas; Weitz, Jürgen; Weigand, Markus A. (Journal of surgical research, 2011)
Background - In this retrospective observational study, we investigated the impact of prior splenectomy on the outcome of patients with complicated peritonitis. - Materials and Methods - Of the 284 subjects with severe sepsis or septic shock due to intra-abdominal infection, 27 (9.5%) had undergone splenectomy before the development of that infection and 257 (90.5%) had not undergone splenectomy. The intra-abdominal source of infection was surgically confirmed (index operation). - Results - The group of patients having undergone splenectomy and that of patients not having undergone the procedure were well balanced in age, gender concomitant disease, as well as medication (prior chemotherapy). Twenty-eight-day estimated mortality did not differ between groups (33.3 versus 25.7%; P = 0.39). Ninety-day estimated mortality did not differ either (57.2 versus 49.7%; P = 0.92). Overall survival was equal between the two groups. More patients having undergone splenectomy required dialysis for renal failure (74.0 versus 44.7%; P < 0.01). A Cox regression analysis left age, sepsis-related organ failure assessment (SOFA) score immediately following index-surgery, and need for administration of norepinephrine exceeding 0.1 μg/kg body weight/min as potential predictors of fatal outcome. - Conclusions - Our results did not support those of earlier reports suggesting that splenectomy protects against polymicrobial sepsis or septic shock. Regarding most effectiveness criteria (28- and 90-d estimated mortality, duration of mechanical ventilation, length of stay in ICU and in hospital), patients having undergone splenectomy fared as well as did those who had not undergone that procedure; regarding some (need for renal replacement), they fared worse. The effect of splenectomy is not large enough to be proven or ruled out with a limited number of cases.
Available online 13 November 2010
Gesehen am 26.08.2022